2005
DOI: 10.1051/0004-6361:20042392
|View full text |Cite
|
Sign up to set email alerts
|

INTEGRAL insight into the inner parts of the Galaxy. High mass X-ray binaries

Abstract: Since its launch INTEGRAL has devoted a significant fraction of its observing time to the Galactic plane region. We present the results of INTEGRAL observations of the inner spiral arms of the Galaxy (Norma, Scutum and Sagittarius) with attention to high mass X-ray binaries. The increased sensitivity of the survey and possibility to detect absorbed sources significantly enlarged our sample of HMXBs in comparison with previous studies. For some absorbed sources we present for the first time high quality broadba… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
130
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 134 publications
(150 citation statements)
references
References 41 publications
19
130
1
Order By: Relevance
“…= 242.6/245). With N H = 1.95 +0.02 −0.03 × 10 24 cm −2 the column density is very high, as is to be expected for this kind of source, and is in agreement with the previous observations (e.g., Lutovinov et al 2005;Walter et al 2006;Ibarra et al 2007). In contrast, the photon index, Γ = 0.676 +0.009 −0.042 , is considerably harder than in several earlier analyses (e.g., Walter et al 2004: Γ = 2.6 or Ibarra et al 2007: Γ = 1.35-1.46).…”
Section: Spectral Analysissupporting
confidence: 92%
See 1 more Smart Citation
“…= 242.6/245). With N H = 1.95 +0.02 −0.03 × 10 24 cm −2 the column density is very high, as is to be expected for this kind of source, and is in agreement with the previous observations (e.g., Lutovinov et al 2005;Walter et al 2006;Ibarra et al 2007). In contrast, the photon index, Γ = 0.676 +0.009 −0.042 , is considerably harder than in several earlier analyses (e.g., Walter et al 2004: Γ = 2.6 or Ibarra et al 2007: Γ = 1.35-1.46).…”
Section: Spectral Analysissupporting
confidence: 92%
“…Matt & Guainazzi (2003) detected intense Fe Kα, Fe Kβ, and Ni Kα emission lines in the spectrum. Based on the interstellar absorption toward the system, which is two orders of magnitude lower than the measured N H , Revnivtsev (2003), Filliatre & Chaty (2004), and Lutovinov et al (2005) also suggested that much of the X-ray absorption is intrinsic to the compact object.…”
Section: Introductionmentioning
confidence: 85%
“…IGR J16465-4507 , discovered with INTEGRAL , is a transient X-ray pulsar (spin period ∼228 s, Lutovinov et al 2005a) which displays on average properties very similar to those of the highly absorbed HMXBs ) but was tentatively associated to the SFXT class due to the detection of fast flaring activity with INTEGRAL (Walter and Zurita Heras, 2007b). The supergiant companion was first identified by Smith (2004) and then confirmed by .…”
Section: Discussionmentioning
confidence: 97%
“…In the majority of HMXBs, pulsations in the X-ray emission firmly established the NSs as accreting compact objects (see, e.g., Lutovinov et al 2005;Lutovinov & Tsygankov 2009, for a recent review and HMXBs statistics), and the detection of cyclotron absorption spectral features permitted directly measuring their magnetic field strength (∼1−5×10 12 G; see, e.g., Coburn et al 2002;Filippova et al 2005;Caballero & Wilms 2012). In the HMXBs that did not show clear evidence of pulsations, black hole companions still cannot be firmly ruled out (see, e.g., the case of 4U 1700-377, Rubin et al 1996;Clark et al 2002).…”
Section: Introductionmentioning
confidence: 99%